Glycated Hemoglobin Variability Is Associated With Adverse Outcomes in Patients With Heart Failure Irrespective of Diabetic Status - Xu, Xin; Ren, Qing‐Wen; Chandramouli, Chanchal; Ng, Ming‐Yen; Tsang, Christopher Tze‐Wei; Tse, Yi‐Kei; Li, Xin‐Li; Liu, Ming‐Ya; Wu, Mei‐Zhen; Huang, Jia‐Yi; Cheang, Iok‐Fai; Yang, Jie‐Fu; et al. (Journal of the American Heart Association, 2024)
The effect of glycated hemoglobin (HbA ) variability on adverse outcomes in patients with heart failure (HF) is unclear. We aim to investigate the predictive value of HbA variability on the risks of all-cause death and HF rehospitalization in patients with HF irrespective of their diabetic status. Using a previously validated territory-wide clinical data registry, HbA variability was assessed by average successive variability (ASV) or SD of all HbA measurements after HF diagnosis. Multivariable Cox proportional hazards models were used to estimate the adjusted hazard ratio (HR) and its corresponding 95% CI. A total of 65 950 patients with HF were included in the study. Over a median follow-up of 6.7 (interquartile range, 4.0-10.6) years, 34 508 patients died and 52 446 required HF rehospitalization. Every unit increment of variability in HbA was significantly associated with higher HF rehospitalization (HR ASV, 1.20 [95% CI, 1.18-1.23]) and all-cause death (HR ASV, 1.50 [95% CI, 1.47-1.53]). Diabetes significantly modified the association between HbA variability and outcomes ( <0.001). HbA variability in patients with HF without diabetes conferred a higher risk of rehospitalization (HR ASV, 1.92 [95% CI, 1.70-2.17] versus HR ASV, 1.19 [95% CI, 1.17-1.21]), and all-cause death (HR ASV, 3.90 [95% CI, 3.31-4.61] versus HR ASV, 1.47 [95% CI, 1.43-1.50] compared with patients with diabetes). HbA variability is significantly associated with greater risk of rehospitalization and all-cause death in patients with HF, irrespective of their diabetic status. These observations were more pronounced in patients with HF without diabetes.